Banco de semillas del suelo y su relación con variables físicas en dos tipos de cobertura vegetal en el parque universitario Francisco Vivar Castro, Loja, Ecuador - Fernández Guerrero, Erendida Marivi (2022)
Montane forests are considered as sites of biodiversity concentration, where many ecological processes need to be investigated, such as soil seed banks (BSS). This reservoir is important because the seeds contained therein are able to remain viable for long periods of time and germinate when environmental conditions are favorable for their development; however, information on these processes is still limited and it is necessary to understand their composition, structure and dynamics. Therefore, the soil seed bank and its relationship with physical variables was studied in two types of vegetation cover in the "Francisco Vivar Castro" University Park, with the objective of understanding the soil seed bank in native forest and forest plantations. The study was carried out in two phases, for the montane forest the monitoring was continued (second phase) for a period of three additional months to those monitored in a previous study; while, for the samples from the plantations, it was developed from January to July 2020. The sampling units (plots) installed by González in 2019 were used for the Pinus radiata plantation, and for the Eucalyptus globulus plantation, it was carried out in the plots implemented by Espinoza in 2019; 50 samples were extracted from the organic and mineral layer, respectively, and then placed in flex foam trays; they were monitored for a period of 180 days; The botanical identification of the species was carried out in the "Reinaldo Espinosa" Herbarium of the National University of Loja; to analyze the relationship between the physical variables and BSS in the montane forest and the forest plantations of the PUFVC, multivariate statistics were used through a principal component analysis (PCA), with the statistical software R Studio in its VEGAN package. In the montane forest, 1,112 individuals belonging to 38 species and 28 families germinated; in the E. globulus plantation, 233 individuals of 25 species of 13 families; and in the P. radiata plantation, 68 individuals of 18 species and 14 families. The seed bank of the montane forest had a Shannon and Pielow index of 2.76 and 0.40 respectively, while in the Eucalyptus plantations 2.63 was obtained for the Shannon index and 0.43 for the Pielow equitability; for the pine plantation 2.52 for the Shannon index and 0.60 for the Pielow equitability. The PCA showed that light significantly influences the germination of the BSS, as well as altitude, since it is a determining physiographic factor in the variation of species richness and composition. The seed bank of the montane forest floor presented the highest number of individuals, species and families, while the forest plantations presented lower values, so the type of cover influences the future floristic diversity of plant remnants. And the physical variables altitude and light are determining factors for the germination of the BSS of the analyzed coverages. Keywords: Soil seed bank, multivariate analysis, floristic composition, Principal Component Analysis, Andean forest.